The Role of Email in Improving Task Performance Among Executives at Multimedia University, Malaysia - Baninajarian, Narges (2009)
Nowadays, one of the most widely used of communication technologies in organization is email. Email expands the communication capabilities that available to employees and in some cases, replaces traditional media such as paper documents, telephone calls, and face-to-face communication. In Malaysia, a large number of high-tech companies have established to promote the Multimedia Super Corridor project. Thus, the assessment of the use and effect of communication technologies in these organizations seems to be relevant. This study aims to examine whether email use has a significant effect on task performance. Specifically, this study attempts to look at how email richness and email ease of use can affect task performance which is determined in four components: decision time, decision quality, consensus, and communication satisfaction. The present study used a survey design to achieve the objectives of the study. Purposive sampling was used to select a total of 239 executives of different faculties and divisions in the Multimedia University. The study used self-administered structured questionnaires as the research instrument. Statistical analyses used in this study were the Chi-Square and Spearman's Rho Correlation. This study revealed that the executives experienced moderate to high level of task performance while using email. There were no significant differences in task performance among respondents based on gender, race, age, education level, position, and work experience categories. The results showed that the executives perceived email in moderate to high level in richness while they perceived email as an easy to use communication medium. The present study has confirmed that email richness and email ease of use have positively significant relationship with task performance. It is indicated that the increase in email richness and email ease of use perception generates an increase in task performance. In terms of email richness, the findings of this study challenge previous studies. It can be concluded that the respondents of this study perceived email as a rich medium and it is a convenient way for them to make decisions. But, for email ease of use as previous studies, the more email is perceived easy to use causes the increasing in task performance. Future studies may focus on the role of new communication technologies in other dimensions of organizational concerns such as social or corporate performance.